2021
DOI: 10.3389/fphar.2021.732540
|View full text |Cite
|
Sign up to set email alerts
|

The miR-130a-3p/TGF-βRII Axis Participates in Inhibiting the Differentiation of Fibroblasts Induced by TGF-β1

Abstract: Pulmonary fibrosis (PF) is a chronic progressive interstitial lung disease that has a poor prognosis. Abnormal activation of transforming growth factor-β1 (TGF-β1) plays a crucial role in fibroblast differentiation. Mesenchymal stem cells (MSCs) are currently being considered for the treatment of PF, but the regulatory mechanisms are poorly understood. We co-cultured bone marrow-derived MSCs and mouse lung fibroblasts (MLg) in the presence of TGF-β1, and studied the protein/mRNA expression of fibrosis markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(52 reference statements)
0
5
0
Order By: Relevance
“… 96 miR-130a-3p inhibits the TGF-β–induced EMT via SMAD4. 97 , 98 miR-21 is involved in the TGF-β1 signaling pathway 99 and suppresses the Hippo signaling pathway. 100 miR-23b-3p activates TGF-β signaling by increasing SMAD2 phosphorylation 101 and regulates autophagy by suppressing SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“… 96 miR-130a-3p inhibits the TGF-β–induced EMT via SMAD4. 97 , 98 miR-21 is involved in the TGF-β1 signaling pathway 99 and suppresses the Hippo signaling pathway. 100 miR-23b-3p activates TGF-β signaling by increasing SMAD2 phosphorylation 101 and regulates autophagy by suppressing SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miRNAs have been extensively studied for their essential role in regulating gene expression at the posttranscriptional level and their relationship with various biological processes [103]. It has been shown that miRNAs play a critical role in developing and progressing multiple lung diseases, such as IPF [103,104]. miR-130a-3p has been shown to participate in the regulation of IPF by inhibiting lung fibroblast differentiation by blocking the activation of the TGF-β/Smad signaling pathway [104].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miRNAs play a critical role in developing and progressing multiple lung diseases, such as IPF [103,104]. miR-130a-3p has been shown to participate in the regulation of IPF by inhibiting lung fibroblast differentiation by blocking the activation of the TGF-β/Smad signaling pathway [104]. Additionally, it has been observed that miR-199a-5p is upregulated in patients with IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that TGF-β1-induced proliferation and differentiation of fibroblasts could be inhibited by miR-130a-3p in the MLG2908 cell line, but whether miR-130a-3p can inhibit the progression of PF in vivo , especially in different phases of PF has not been established ( Liu et al, 2021 ). The aim of the present study was to explore the anti-inflammatory and anti-fibrotic effects of miR-130a-3p by examining the activity of the NF-κB and TGF-β1/Smad signaling pathways, which would provide a new therapeutic approach to prevent and perhaps even partially reverse the occurrence and progression of PF.…”
Section: Introductionmentioning
confidence: 99%